Chlorophyll a and phaeophytin a measurements from discrete water samples during RV HEINCKE cruise HE662 - Albinus, Michelle; Raffelt, Lukas; Sawle, Shubham; Badewien, Thomas Henry (PANGAEA, 2025)
This dataset was collected during the cruise HE662 (24.05.2025 to 13.06.2025) with RV HEINCKE from Bremerhaven, Germany to Bremerhaven, Germany. It contains chlorophyll a measurements [µg/l] from water samples collected from discrete sampling via CTD. In total, 27 samples have been collected. To obtain chl-a concentrations water samples were filtered onboard through 0.7 µm pore size, glass fiber filters (Whatman GF/F) under low vacuum. Filters were frozen immediately at -80 °C until extraction in laboratory by 90% acetone method (measured on 07.08.2025). Concentrations were calculated from fluorescence measured with a pre-calibrated Turner Design TD 7200-02 laboratory fluorometer (EPA445.0, Turner Manual). Calibration details are given in the attached calibration document (PDF).
Keywords: Baltic Sea; Chlorophyll a; Fluorescence; Phaeophytin a